2022
DOI: 10.1021/jacs.1c13569
|View full text |Cite
|
Sign up to set email alerts
|

An N-Fluorinated Imide for Practical Catalytic Imidations

Abstract: Catalytic imidation using NFSI as the nitrogen source has become an emerging tool for oxidative carbon–nitrogen bond formation. However, the less than ideal benzenesulfonimide moiety is incorporated into products, severely detracting its synthetic value. As a solution to this challenge, we report herein the development of a novel N-fluorinated imide, N-fluoro-N-(fluorosulfonyl)­carbamate (NFC), by which the attached imide moiety acts as a modular synthetic handle for one-step derivatization to amines, sulfonam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 79 publications
(100 reference statements)
0
14
0
Order By: Relevance
“…In particular, our group is developing practical N–F reagents bearing easily deprotectable substituents on the nitrogen atom to replace NFSI. 10 Recently, Aikawa and Hashimoto et al reported a novel N–F reagent, N -fluoro- N -(fluorosulfonyl)carbamate (NFC). 10 b With this N–F reagent, the elimination of fluorine allowed the transformation of arenes and alkenes to amines whose nitrogen atoms were protected by the sulfonyl and alkoxycarbonyl moieties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, our group is developing practical N–F reagents bearing easily deprotectable substituents on the nitrogen atom to replace NFSI. 10 Recently, Aikawa and Hashimoto et al reported a novel N–F reagent, N -fluoro- N -(fluorosulfonyl)carbamate (NFC). 10 b With this N–F reagent, the elimination of fluorine allowed the transformation of arenes and alkenes to amines whose nitrogen atoms were protected by the sulfonyl and alkoxycarbonyl moieties.…”
mentioning
confidence: 99%
“…The novel N–F reagents bearing Ns group(s) were synthesized as summarized in Scheme 2. 10,12 The fluorination of lithium sulfonimides ( 2a – c ) substituted by Ns/Ns, Ns/ p -Ns and Ns/Ms (methanesulfonyl) groups was carried out by using N 2 -diluted F 2 (2 vol%) in acetonitrile/H 2 O at 0 °C, affording the corresponding products 1a – c in high yields (84–99%) (Scheme 2a). Lithium salt 2f , readily prepared from commercially available N -( tert -butoxycarbonyl)-2-nitrobenzenesulfonamide, was also converted to N -fluorinated product 1f under the same reaction conditions.…”
mentioning
confidence: 99%
“…Recent examples are Fier's reagent (R12) for alpha-carbamation of pyridines 29 and an improved version of NFSI by the Hashimoto group (NFC, R16). 178 In most cases, hydroxylamine-derived reagents exhibit scalable syntheses, air and temperature stability and a broad range of applications. Their practicality is further increased as they tend to be easy-to-handle solids with an extended shelf life.…”
Section: Discussionmentioning
confidence: 99%
“…Recent examples are Fier's reagent (R12) for alpha-carbamation of pyridines 29 and an improved version of NFSI by the Hashimoto group (NFC, R16). 178 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation